Legal Analysis of Tobacco Dispute Between Indonesia vs United States Under Wto Relating to National Treatment Principles - Dewi, Sinta (UI Scholars Hub, 2011)
This article discusses the disputes between Indonesia vs United States under the WTO relating to the application of United States National Regulation on the Family Smoking Protection and Tobacco Act, 2009 in prohibiting the production or sale of clove cigarettes. Currently, WTO is to rule on Disputes and the Panel has been established to settle the disputes. The main objectives of this article to analyze national treatment principles under the WTO agreement and General Exception under Article XX WTO as one of the basic legal claims submitted by Indonesia.This article will study and analyze how far the WTO obligations will be applied in that case. The Article organized as follows, first, discuss the national treatment obligation and general exception under the WTO Rule, second, analyzing the similar cases under the GATT and WTO Dispute Setlement. Finally, the article will be analyzing the Tobacco disputes.